MINAT BELAJAR IPA SISWA KELAS IV SD NEGERI 93 CABBENG KECAMATAN DUA BOCCOE KABUPATEN BONE - Sudarto Sudarto; Asriadi; Asmar Masdiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research is a qualitative research that aimed to describe the interest in learning science for fourth grade students at SD Negeri 93 Cabbeng, Dua Boccoe District, Bone Regency. The subjects of this study were teachers (1 person) and fourth grade students (14 people). Research data obtained by interview and questionnaire techniques. Data analysis includes data reduction, data presentation and drawing conclusions. The results showed that the interest in learning science for grade IV students at SD Negeri 93 Cabbeng, Dua Boccoe District, Bone Regency was based on the following indicators: (1) arriving on time, (2) preparing the books, (3) sitting quietly, (4) participating in early learning, (5) keep the spirit, (6) take the learning seriously, (7) do the homework, (8) clean up the class, (9) record the important things, (10) giving answer when he/she asked by his/her teacher, (11) work in groupand (12 ) keeping the class atmosphere calm, generally students were interested. Whereas in the indicators: (1) following the science learning process to the end, (2) doing assignments during learning, (3) teaching his/her friends if he/she asked byhis/her teacher, (4) listening or paying attention to the teacher, and (5) asking the teacher if there are things that is not understood were the students generally less interested. Conclusion: Science learning interest of the students in Fourth Grade at SD Negeri 93 Cabbeng, Dua Boccoe District, Bone Regency in learning the science still needs to be improved.